GERAKAN MENDIDIK ANAK BAGI IBU RUMAH TANGGA DI KEL. FOBAHARU KEC. TIDORE UTARA KOTA TIDORE KEPULAUAN PROV. MALUKU UTARA - Agus, Agus; Ahmad, Samlan Hi; Kodja, Jufri; Asnawi, Nur Rahmah (Al-Mulk: Jurnal Pengabdian Masyarakat, 2023)
Educating children requires separate methods and approaches from parents. Therefore housewives must be aware of their duties and responsibilities. Not a few parents pay less attention to their children's education. Some of the things behind the lack of education given by parents to their children include economic, social (association), cultural and political factors. The resulting impact requires assistance from educational practitioners. That is why it is very important to do Community Service in the Fobaharu Village, Kec. North Tidore City of Tidore Archipelago. The purpose of this PkM is to describe 1) The activity of opening the Movement to Educate Children for Housewives in Kel. Fobaharu Kec. North Tidore Tidore City Archipelago North Maluku Province 2) Provision of materials to housewives in Kel. Fobaharu Kec. North Tidore Tidore City Archipelago North Maluku Province 3) Closing activities of the Movement to Educate Children for Housewives in Kel. Fobaharu Kec. North Tidore City of Tidore Archipelago North Maluku Province. The PkM implementation method is carried out in 3 stages, namely the preparation or opening stage of the activity, delivery of material and closing of the activity. From these stages resulted in 1) The opening activity was carried out by reading the holy verses of the Koran, singing the Indonesiaraya song, salawat, remarks and the event was opened by the Head of Kelurahan Fobaharu Kec. North Tidore City of Tidore Archipelago. 2. Material delivery activities by the team with the theme of the blue echo background, the direction of the blue echo and the blue echo as a moral fortress. 3) Closing activities are carried out by reciting verses from the holy Koran, reading prayers, messages from representatives of PkM participants and closing by the head of Keluran Fobaharu Kec. North Tidore.Keywords: Movement; Educate; Child; Housewife.